2005
DOI: 10.1139/w05-093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization of selected prokaryotic S-layer proteins

Abstract: Regular crystalline surface layers (S-layers) are widespread among prokaryotes and probably represent the earliest cell wall structures. S-layer genes have been found in approximately 400 different species of the prokaryotic domains bacteria and archaea. S-layers usually consist of a single (glyco-)protein species with molecular masses ranging from about 40 to 200 kDa that form lattices of oblique, tetragonal, or hexagonal architecture. The primary sequences of hyperthermophilic archaeal species exhibit some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 72 publications
0
52
1
Order By: Relevance
“…Up to now, very little is known concerning the composition and modification of the surface layer proteins from Thermococcales species; however, it has been reported that S-layer proteins of hyperthermophilic archaea have more charged residues than their mesophilic counterparts and that S-layer glycoproteins in archaeal halobacteria contain sulfated glucuronic acid residues (10). Altogether, this suggests that ORFs 676 and 678 are exposed to the surface of the enveloped virion and might be implicated in host recognition and attachment via the binding capacity of the LamGL domain to sulfated glycoproteins exposed to the surface of P. abyssi.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, very little is known concerning the composition and modification of the surface layer proteins from Thermococcales species; however, it has been reported that S-layer proteins of hyperthermophilic archaea have more charged residues than their mesophilic counterparts and that S-layer glycoproteins in archaeal halobacteria contain sulfated glucuronic acid residues (10). Altogether, this suggests that ORFs 676 and 678 are exposed to the surface of the enveloped virion and might be implicated in host recognition and attachment via the binding capacity of the LamGL domain to sulfated glycoproteins exposed to the surface of P. abyssi.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was noted that the S-layer glycoproteins of the hyperthermophiles Mcc. jannaschii and Methanotorris igneus contain a higher number of potential N-glycosylation sites than the same protein in mesophilic species (167,226). While this observation underscores the potential contribution that N-glycosylation makes to protein thermostability, thermal stabilization of S-layer glycoproteins may not rely solely on glycosylation density and/or the composition of the N-glycan but may also be attributed to phosphorylation, salt bridging, or covalent cross-linking (227).…”
Section: Biological Effects Of N-linked Glycosylation Perturbations Imentioning
confidence: 92%
“…The structural and functional aspects of S-layers have been discussed in a number of comprehensive articles (Sára and Egelseer, 1996;Beveridge et al, 1997;Engelhardt and Peters, 1998;Sára and Sleytr, 2000;Claus et al, 2005;König et al, 2007). This study is an attempt to reconsider assumptions on S-layer functions in the view of new insights and of mutual effects between cell envelope components.…”
Section: Introductionmentioning
confidence: 99%